On God and the Beginning of the Universe: An Evaluation of Recent Discussions - Loke, Andrew Ter Ern (Religions, 2023)
Philosophical analysis is of vital importance for addressing the controversies in science and theology. This article evaluates the analyses concerning God and the beginning of the universe offered by a number of philosophers. It is shown that, while Linford is correct in that establishing that physical reality has a finite past is not sufficient for establishing that physical reality had a beginning, the objections which Linford, Schmid, Oberle, and Wielenberg have offered against the Cosmological Argument for the existence of God can be rebutted. The examination of the objections and rebuttals demonstrates how a more careful philosophical analyses of the issues concerning the argument against infinite causal regress, personal identity, timelessness, the definition and reducibility of time, and the causal principle can contribute to the interaction between science and theology.